PROMOSI DALAM MENINGKATKAN VOLUME PENJUALAN TINJAUAN MANAJEMEN SYARIAH - Yosy Arisandy (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
This study aims to determine:Management reviews the increase in sales volume sharia use as a promotional marketing mixvariables.This type of research is a field research using a combined approach between Qualitative and quantitative associative. With purposive sampling technique sampling, collecting data through observation, surveys, and literature as well as data analysis techniques to test the quality of data, hypothesis testing and coefficient determinasi.Jumlah sample in this study is 30 people. The results showed that the Promotion (X) significant positive effect on sales volume (Y), it is shown from the results of the t test with significant value 0.000 <0.05 .. The amount of influence Promotion (X) on sales volume (Y) correlation coefficient R = 0.488 (48.8%) were influenced by other variables that are not included in this study. Islam permits commerce, but with honesty in its activities including the promotion of the marketing mix.